2019
DOI: 10.1088/1741-4326/ab0755
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale interaction of pedestal instabilities in H-mode plasma on the EAST tokamak

Abstract: A cross-scale interaction between a kink instability with toroidal mode number (n) of 1 and background microturbulence (mainly a coherent mode with n  =  12–17) has been observed in the H-mode edge pedestal region in the EAST tokamak. The n  =  1 kink mode with a frequency ~3.5 kHz is localized in the pedestal region. The amplitude of pedestal microturbulence is evidently modulated at the frequency of the n  =  1 mode. This amplitude modulation is mainly for the fluctuation component with frequency less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For the EAST tokamak, the density inversion method for lithium beam probe is under optimization. The ECE system can only provide reliable pedestal top temperature even though there is no fast-electron interference induced by LHCD (due to the quick drop in optical thickness in the pedestal [25,26]). Instead, the perturbations on the edge extreme ultraviolet (XUV) radiation induced by ELMs have been included here.…”
Section: Radial Extent Of Perturbations Induced By Small Grassy Elmsmentioning
confidence: 99%
“…For the EAST tokamak, the density inversion method for lithium beam probe is under optimization. The ECE system can only provide reliable pedestal top temperature even though there is no fast-electron interference induced by LHCD (due to the quick drop in optical thickness in the pedestal [25,26]). Instead, the perturbations on the edge extreme ultraviolet (XUV) radiation induced by ELMs have been included here.…”
Section: Radial Extent Of Perturbations Induced By Small Grassy Elmsmentioning
confidence: 99%
“…Tearing modes modulate turbulence and the plasma flow in the plasma core, as reported in tokamaks [16][17][18][19][20][21]. Furthermore, there are investigations of turbulence coherent structures modulated by the kink instability and micro-turbulence modulated by the lowfrequency mode (LFM) in the H-mode pedestal region [22,23]. Turbulence and plasma flows are known to be modulated by MHD modes in different confinement regimes and regions indicating common features of cross-scale interaction, which is of significant importance for further study in order to find possibilities to control turbulence and induced transport.…”
Section: Introductionmentioning
confidence: 92%
“…It was found that the pedestal width of EAST ELMy H-modes is wider than that of DIII-D but there is also a good correlation with the square root of pedestal poloidal beta β 1/2 p,ped [19]. The experimental studies found that the appearance and disappearance of the CM was correlated to the pedestal pressure on EAST [22,25]. This article mainly focuses on the preliminary research on the pedestal width and height of the selected H-mode discharges, and further try to use the REPED model to predict the pedestal height for EAST H-mode plasmas.…”
Section: Introductionmentioning
confidence: 95%